A Common Currency for Belarus and Russia? - Prokopenko, Vassili; Gulde, Anne.; Jafarov, Etibar (Washington, D.C. : International Monetary Fund, 2004)
This paper discusses costs, benefits, and implementation challenges of a possible currency union between Belarus and Russia. It shows that Belarus and Russia are economically closely linked but nevertheless do not fulfill all "optimal currency area" criteria, especially the macroeconomic symmetry condition. Furthermore, we argue that the different speeds of economic liberalization over the past decade have resulted in different economic structures, with Belarus still dependent on monetary financing of budgets and industries. However, a final cost-benefit analysis also needs to consider that currency unification may bring substantial benefits from reduced transaction costs, an improved macroeconomic environment in Belarus, and by acting as a catalyst to advance structural reforms in Belarus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet